Pengaruh Sistem Pengukuran Kinerja Non Keuangan, Keadilan Distributif, Keadilan Prosedural Terhadap Kinerja Individu Pada Rumah Sakit Di Kota Bandar Lampung - Eferedy, Jhon; Yuliansyah, Yuliansyah; Luthfi, Muhammad (Universitas Malahayati, 2024)
This study aims to provide empirical evidence about the effect of Non-Financial Performance Measurement Systems, Distributive Justice, Procedural Justice on Individual Performance in Hospitals in Bandar Lampung City. Through this research, it can be seen (1) the positive influence between Non-Financial Performance Measurement Systems on Distributive Justice, (2) the positive influence between Non-Financial Performance Measurement Systems on Procedural Justice, (3) To obtain empirical evidence about the positive influence of Distributive Justice on Performance Individuals, (4) positive influence between procedural justice on individual performance in hospitals in Bandar Lampung City. This type of research is classified as qualitative research. The population in this study is a hospital located in the city of Bandar Lampung based on data obtained from online hospital data, which amounted to 20 hospitals. The sample is determined based on nonprobability sampling technique, as many as 100 samples. Data obtained through direct questionnaire dissemination. Data analysis techniques with Partial Leasrt Square (PLS) are using SmartPLS software.The results of this study conclude: (1) the non-financial performance measurement system has a significant influence on distributive justice, (2) the non-financial performance measurement system has a significant effect on procedural justice, (3) distributive justice has a significant influence on individual performance, (4) procedural justice has a significant influence on individual performance in hospitals in Bandar Lampung City. Based on the above research, it is suggested: for further research to add other factors that might be interesting to test include financial performance measurement systems, or organizational justice and can expand the object of research.